Pendekatan Komunikasi dalam Program Bimbingan Perkawinan sebagai Upaya Pencegahan Stunting - Evi Zulfiana; Nora Rahmanindar (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The high rate of stunting in 2025 in the Labaksiu sub-district prompted the government to involve the Office of Religious Affairs (KUA) in stunting prevention efforts. This is based on the view that the process of forming a family is closely related to childbearing, so the KUA was revitalized to include stunting issues in marriage guidance materials. This study aims to examine the communication strategies used in the marriage guidance program to prevent stunting in the Labaksiu sub-district. The method used is qualitative descriptive, with data collected through in-depth interviews with six informants, consisting of three guidance facilitators, one health officer, and two program participants. The study's findings indicate that the communication strategy in the marriage guidance program for stunting prevention refers to Lasswell's theory, emphasizing the role of a competent communicator, namely a certified facilitator. The material presented covers topics on reproductive health and the development of outstanding generations, delivered in an educational and persuasive manner. The media used include modules and direct delivery by facilitators. The target of the program is prospective couples who have registered at the KUA. The impact of this program is an increase in the knowledge of prospective brides and grooms regarding the importance of preparing for a healthy family.